Answer:
Centre = (1, 3)
radius = 8units
Step-by-step explanation:
The standard equaton of a circle is expressed as;
![x^2+y^2+2gx+2fy+C\text{ = 0}](https://img.qammunity.org/2023/formulas/mathematics/college/wjkbufsdf8by4cx4c35uwmp6f331m7tt09.png)
The radius of the circle is expressed as;
![r=\sqrt[]{g^2+f^2-C^{}}](https://img.qammunity.org/2023/formulas/mathematics/college/usnp69j7huc47ueykobaqqzcd5kdjqq74m.png)
The centre is at C(-g, -f)
Given the expression;
![x^2+y^2-2x-6y-54=0](https://img.qammunity.org/2023/formulas/mathematics/college/qv596ay8kjb3bjtf7djwk075mx8pb23sdz.png)
Get the centre of the circle.
Compare both equations
![\begin{gathered} 2gx=-2x \\ g\text{ = -1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6rrr71xfguwvogfplta8q3h6jb8v0hs589.png)
similarly;
![\begin{gathered} 2fy=-6y \\ 2f=-6 \\ f=-(6)/(2) \\ f=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lmow44gq0era45qj1ceobv8mxys29ijwoq.png)
The centre will be located at C(-(-1), -(-3)) = C(1, 3)
Next is to get the radius
Recall;
![\begin{gathered} r=\sqrt[]{g^2+f^2-C} \\ r=\sqrt[]{(-1)^2+(-3)^2-(-54)} \\ r=\sqrt[]{1+9+54} \\ r=\sqrt[]{64} \\ r=8\text{units} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/60ad8qtw7n7o87eroguip492c4zdu5psh7.png)
Hence the radius is 8units